Further refining 2020 ESGO/ESTRO/ESP molecular risk classes in patients with early‐stage endometrial cancer: A propensity score–matched analysis. Issue 15 (26th May 2022) - Nero, Camilla; Pasciuto, Tina; Cappuccio, Serena; Corrado, Giacomo; Pelligra, Silvia; Zannoni, Gian Franco; Santoro, Angela; Piermattei, Alessia; Minucci, Angelo; Lorusso, Domenica; Fanfani, Francesco; Scambia, Giovanni
Abstract : Background: The integration of molecular features with clinicopathological findings in endometrial cancer classification seems to be able to significantly refine risk assessment. Nevertheless, clinical management remains challenging, and different therapeutic options are available for each class. Further prognostic characterization of the subgroups within each risk class could be helpful in the decision‐making process. Methods: This study evaluated the role of the 2020 European Society of Gynaecological Oncology (ESGO)/European Society for Radiotherapy and Oncology (ESTRO)/European Society of Pathology (ESP) risk assessment system and the three prognostic profiles adopted in the PORTEC‐4a trial in predicting disease‐free and overall survival in a retrospective study cohort of patients with early‐stage endometrial cancer. Patients were selected according to a 1:2 propensity score matching analysis. Moreover, the sequencing of 29 genes was undertaken for tumor samples. Results: The study included 137 patients. No differences in disease‐free or overall survival at 5 years were observed among the 2020 ESGO/ESTRO/ESP risk classes without molecular features ( p  = .766 and p  = .176, respectively). Once molecular features were integrated, the probability of overall survival was significantly different ( p  = .011). When the three prognostic profiles were applied, the probability of recurrence had a p value of .097, and significant differences were observed in overall survival ( p  = .004). Among patients experiencing recurrence, 17.6% showed mutations in BRCA1/2, RAD50, BRIP1, and XRCC2, whereas 22.5% had PD‐L1–positive expression and an MUTYH mutation. Conclusions: Further stratification within each risk class according to the most relevant prognostic features could better define the prognosis of patients with early‐stage endometrial cancer. Nearly half of the patients who experienced recurrence showed a targetable molecular alteration for which dedicated trials should be encouraged. Abstract : The 2020 molecular integrated risk assessment is of crucial importance for better defining the prognosis of patients with early‐stage endometrial cancer. Nevertheless, further stratification within each risk class according to the most relevant prognostic features could better define the biological behavior of the disease and thus allow better tailoring of adjuvant treatment.